Spatial and temporal controls on proglacial erosion rates: A comparison of four basins on Mount Rainier, 1960 to 2017. Issue 2 (23rd November 2021) - Anderson, Scott W.; Shean, David
Summary: The retreat of alpine glaciers since the mid‐19th century has triggered rapid landscape adjustments in many headwater basins. However, the degree to which decadal‐scale glacier retreat is associated with systematic or substantial changes in overall coarse sediment export, with the potential to impact downstream river dynamics, remains poorly understood. Here, we use repeat topographic surveys to assess geomorphic change in four partly glaciated basins on a stratovolcano (Mount Rainier) in Washington State at roughly decadal intervals from 1960 to 2017. The proglacial extents of the four basins show distinct geomorphic trajectories, ranging from substantial and sustained net erosion to relatively inactive with net deposition. These different trajectories correspond to differences in initial (1960) valley floor gradients, and can be effectively understood as valley floor grade adjustments. Significant erosion was most often accomplished by debris flows triggered by extreme rainfall or glacial outburst floods, though a single rockfall mobilized more material than all other events combined. Year‐to‐year runoff events had little measurable geomorphic impact. Exported material tended to accumulate in broad deposits within several kilometers of source areas and largely remained there through the end of the study period. Over 10‐ to 100‐year timescales, we find that the impact of glacier retreat on coarse sediment yield may then vary substantially according to the geometry and storage trends of the newly exposed valley floor; the timing of that response may also be dictated, and potentially obscured, by stochastic and/or extreme events. Abstract : High‐resolution topography, primarily generated from historical aerial imagery, was used to document geomorphic change in four proglacial basins on Mount Rainier back to 1960. Valley gradient emerges as a key control on cross‐basin variations in recent erosion rates, though the timing of erosion was largely driven by episodic extreme events. Together, this implies that the impact of glacier retreat on sediment yields is likely both stochastic and spatially variable over decadal timescales.